Atezolizumab plus bevacizumab and chemotherapy versus bevacizumab plus chemotherapy for metastatic cervical cancer: a cost-effectiveness analysis - Cai, Hongfu; Fang, Ling; Lin, Jingwen; Zheng, Zhiwei (Frontiers in Pharmacology, 2024)
Aim：The objective of this study is to conduct a cost-effectiveness analysis in order to evaluate the economic advantages of incorporating atezolizumab into a standard bevacizumab plus platinum regimen for the treatment of metastatic cervical cancer from the Chinese medical system perspective. Method: We developed a partitioned survival model based on data obtained from the recently published BEATcc clinical trial and economic cost data. Our model utilized a tree-based decision analysis approach to simulate two different treatment strategies for metastatic cervical cancer: the standard bevacizumab plus platinum regimen, and the addition of atezolizumab to the standard treatment regimen. The economic assessment data included the costs of the drugs, costs related to treatment-induced adverse events. The cost-effectiveness metrics used in the analysis were quality-adjusted life-year (QALY) and incremental cost-effectiveness ratio (ICER). The robustness of our model was assessed through sensitivity analysis. Result：The total costs of the atezolizumab group were $128,179.56, while the costs of chemotherapy group were $42,065.89. The atezolizumab group gained 3.52 QALYs, whereas the chemotherapy group gained 2.35 QALY. The atezolizumab regimen resulted in an increase of 1.17 QALYs at an incremental cost of $86,113.67. This led to an ICER of $73,601.43, which exceeds the willingness-to-pay (WTP) threshold of $39,855.79 in China. Sensitivity analysis demonstrated none of the parameters within a margin of ±25% result in significant alterations to the analysis findings. Conclusion：Atezolizumab plus bevacizumab and chemotherapy was not to be a cost-effective option for the treatment of metastatic cervical cancer compared to bevacizumab plus chemotherapy.